PERAN TEKNOLOGI INFORMASI DALAM PENGEMBANGAN SISTEM INFORMASI AKUNTANSI (SIA) SEBAGAI SARANA PENINGKATAN KINERJA PERUSAHAAN - Ira Setiawati (STIE Pelita Nusantara Semarang, 2007)
Recently, Competitive Advantages is a participated form of organizations to extent the quality, management performance and a business competition strategy. There are many ways to achieave the competitive advantages, one of this is information technology developing. Now, We think that how to create an Information system usefull as a decision making to improve management performance. Accounting Information System (AIS) is one of the oldest Information System and used to calculate and manage of accounting files. We hope that the accounting information can reported accurate and quickly.